2017
DOI: 10.1111/tri.12913
|View full text |Cite
|
Sign up to set email alerts
|

Transplant size mismatch in restrictive lung disease

Abstract: Structured Abstract Background To maximize the benefit of lung transplantation, the effect of size mismatch on survival in lung transplant recipients with restrictive lung disease (RLD) was examined. Methods All single and bilateral RLD lung transplants from 1987–2011 in the UNOS Database were identified. Donor pTLC:Recipient pTLC ratio (pTLCr), quantified mismatch. pTLCr was segregated into 5 strata. A Cox proportional hazards model evaluated the association of pTLCr with mortality hazard. To identify a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…As in our study, donor age> 55 years and prolonged ischemic times have also been associated with worse survival outcomes [ 33 ], and donor age> 50 years has been independently associated with decreased survival [ 34 ]. In cases of differences in donor and recipient lung size, and when Taylor reduction surgery was sometimes necessary, x30 (Taylor measure, 1.34), in accordance with other studies, this size discrepancy increased mortality in cases of single undersized lung transplantation [ 35 ].…”
Section: Resultssupporting
confidence: 77%
“…As in our study, donor age> 55 years and prolonged ischemic times have also been associated with worse survival outcomes [ 33 ], and donor age> 50 years has been independently associated with decreased survival [ 34 ]. In cases of differences in donor and recipient lung size, and when Taylor reduction surgery was sometimes necessary, x30 (Taylor measure, 1.34), in accordance with other studies, this size discrepancy increased mortality in cases of single undersized lung transplantation [ 35 ].…”
Section: Resultssupporting
confidence: 77%
“…Finally, comparing the results to Dalian City in Liaoning Province, another city in northeastern China, this study found lower rates of initial multidrug resistance (2.9%) and retreatment multidrug resistance (10.2%) compared to Dalian City's rates of 5.8% and 17.7%, respectively. This indicates that Jilin Province has a lower drug resistance rate and demonstrates effective control measures (Ganapathi et al, 2017;Wang et al, 2019). Overall, the drug resistance rates of both initially diagnosed and retreatment cases have decreased in recent years, but the decrease is more significant in initially diagnosed cases, while the drug resistance rate among retreatment cases continues to rise (Duan et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…2 However, in recipients with restrictive lung disease specifically, single lung transplant recipients who received a donor lung with a lower or higher predicted total lung capacity and bilateral lung transplant recipients of slightly oversized lungs have a higher risk of mortality. 3 Due to limitations of database granularity, the role of diaphragm plication in these previous studies cannot be assessed, even though it was likely performed in some patients.…”
Section: Editorial: Discerning the Role Of Diaphragm Plication In Lun...mentioning
confidence: 99%
“…Convincing data from previous studies examining the ratio of donor‐to‐recipient predicted total lung capacity suggests that in recipients not categorized according to primary diagnosis, slightly oversized lung allografts are associated with improved survival after bilateral lung transplant 2 . However, in recipients with restrictive lung disease specifically, single lung transplant recipients who received a donor lung with a lower or higher predicted total lung capacity and bilateral lung transplant recipients of slightly oversized lungs have a higher risk of mortality 3 . Due to limitations of database granularity, the role of diaphragm plication in these previous studies cannot be assessed, even though it was likely performed in some patients.…”
mentioning
confidence: 99%